2016
DOI: 10.1038/lsa.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

Control over emissivity of zero-static-power thermal emitters based on phase-changing material GST

Abstract: Controlling the emissivity of a thermal emitter has attracted growing interest, with a view toward a new generation of thermal emission devices. To date, all demonstrations have involved using sustained external electric or thermal consumption to maintain a desired emissivity. In the present study, we demonstrated control over the emissivity of a thermal emitter consisting of a film of phase-changing material Ge2Sb2Te5 (GST) on top of a metal film. This thermal emitter achieves broad wavelength-selective spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
184
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(199 citation statements)
references
References 61 publications
(35 reference statements)
1
184
0
Order By: Relevance
“…Most researchers are interested in Ge 2 Sb 2 Te 5 due to its faster crystallization rate, lower power consumption, as well as the undemanding composition requirements that minor composition deviation does not affect the performance. [14][15][16] Our research focuses on tracking the GST optical constant evolution process during the successive stages of phase-change. As there are coexistence of different proportion of amorphous and crystalline phases at different phase transformation stages.…”
Section: 10mentioning
confidence: 99%
“…Most researchers are interested in Ge 2 Sb 2 Te 5 due to its faster crystallization rate, lower power consumption, as well as the undemanding composition requirements that minor composition deviation does not affect the performance. [14][15][16] Our research focuses on tracking the GST optical constant evolution process during the successive stages of phase-change. As there are coexistence of different proportion of amorphous and crystalline phases at different phase transformation stages.…”
Section: 10mentioning
confidence: 99%
“…Du et al recently reported GST–Al bilayer and Cr–GST–Au trilayer structures as wavelength‐tunable mid‐infrared thermal emitters . Importantly, using measured material properties of GST, the authors studied the absorption evolution of the two structures as a function of the degrees of crystallization of GST, which facilitates the continuously tunable emissivity of the proposed devices undergoing different annealing processes.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…It is difficult to tune the peak wavelength in such structures, and the emissivity can only be tuned in a limited range from 50% to 80% when the temperature increases from 293 K to 623 K. The thickness of the whole structure is as large as 2 μm (∼0.4λ) in order to suspend top metamaterial pattern above the ground plane. (3) By thermally controlling the phases of phase‐changing materials like Ge2Sb2Te5 (GST) and VOx at different temperatures, tunable thermal emission can be realized based on multilayer structures. The peak wavelength tuning is dependent on the thickness of GST or VOx and the thermal emitters thus present comparatively low design flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The ultrathin feature is achieved by adopting the MIM plasmonic metamateirals, in which the emission wavelength can be controlled by the geometric size of top metallic particles without sacrificing the total device thickness. The dynamic low‐power‐consumption control is implemented by incorporating zero‐static‐power phase‐changing material Ge2Sb2Te5 (GST), which has been applied in various energy‐efficient switchable photonic devices . The whole structure shows a total thickness of 550 nm (∼0.023λ), which is well below the subwavelength scale.…”
Section: Introductionmentioning
confidence: 99%